GENOTYPING AND ANALYSIS OF rs7501939 POLYMORPHISM FOR PROSTATE CANCER - Ozkan, Ebru; Erdemir, Aysegul; Torer, Bugra Dogukan; Tasci, Ali Ihsan; Baskin, Yasemin; Ellidokuz, Hulya; Balik, Dilek Turgut (YILDIZ TECHNICAL UNIV, 2015)
Prostate cancer is the second most common cause of death from cancer among men in Turkey. It is known that genetics plays a critical role in prostate cancer susceptibility. Several genome wide association studies reported that rs7501939 polymorphism was significantly associated with prostate cancer. To confirm association of rs7501939 alleles with prostate cancer in our population, genotyping was conducted by using the iPLEX assay in study group which consists of 85 prostate cancer patients and 90 healty controls. In this study, previous reports of rs7501939 variant association with prostate cancer was not confirmed for our population. The odds ratio for prostate cancer was 0,75 (95% CI=0,48-1,18) for carriers of any T allele compared with noncarriers (p=0,211). Chi square and Fisher's exact test results showed that rs7501939 variant was not statistically associated with clinico-pathological variables of prostate cancer patients in our population.
Keywords: Prostate cancer; single nucleotide polymorphism (SNP); SNP genotyping; Engineering